Say the Sound - Murray, W.; Illustrated by Wingfield, J. H. (London Ladybird)
Uses the most frequently met words in the English language as a starting point for learning to read successfully and confidently. This book provides the link with writing for the words used in readers "4a" and "4b".
Include Color Illustrations
Keywords: Readers (Elementary)